Let's Get Real - Garcia, J. Neil C. (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
In this keynote given at the First National Queer Studies Conference, sponsored by the Center for Gender and Women’s Studies of the University of the Philippines in November 2020, the author presents his reflections on the (anglophonic) conditions of possibility of this field of inquiry in a cultural location such as ours—one that is characterized by the cultural and linguistic simultaneities that the translational processes of coloniality and its aftermath must engender. After reviewing the social history of “queer” as a political category, the author discusses the implications of its translational fate in the Philippines, in the process offering new and radically specific possibilities of its enactment within both a postcolonial and a decolonial framework.